(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article is devoted to the definition of the concept of a transaction of admission of accusation and of cooperation in Russian criminal proceedings. The practicality of fixing in the Russian criminal procedure legislation of the procedure for the implementation and implementation of a transaction on the admission of charges, which is widely known and often used in criminal proceedings in a number of countries.